A Cross-Sectional Study of the Relationship between Work Endurance and IQ Level of Medical Students of Universitas Islam Malang - Amelia Amelia; Anita Puspa Widiyana (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2026)
Medical students must maintain prolonged mental strain and different cognitive loads. Previous research has focused primarily on studying different types of intelligence and its relation to academic success and more specifically to grade point average (GPA). Yet, this leaves several questions unanswered. Most empirical research has concentrated on academic achievements and not on the psychological construct of stamina. Most of the research studies in this area focused in the western countries, and hardly any evidence exists on medical students from poorer countries. Most research in this area focused on academic achievement and failed to use psychometric tests assessing intelligence and the stamina construct. It also remains open question for academic research to explore the relationship between cognitive intelligence and work endurance. This study focused on the relationship of the emerged psychological construct and intelligence quotient (IQ) of medical students in Universitas Islam Malang, Indonesia. A cross-sectional analytic study was done on medical students who fulfilled the inclusion criteria. Absolutely, IQ was evaluated by the Culture Fair Intelligence Test (CFIT) and work endurance was evaluated by the Kraepelin Test. The data was processed by correlation analysis. The results indicated that there was no statistically significant correlation between activity endurance and IQ (p > 0.05). This measurement shows that both intelligence and activity endurance are distinct psychological variables. This indicates that the cognitive element of a student’s personality may not be sufficient to explain the student’s ability to maintain prolonged academic effort.